Procrastination in teams, contract design and discrimination - Philipp Weinschenk (Max Planck Institute for Research on Collective Goods, 2011)
We study a dynamic model of team production with moral hazard. We show that the players begin to invest effort only shortly before the time limit when the reward for solving the task is shared equally. We explore how the team can design contracts to mitigate this form of procrastination and show that the second-best optimal contract is discriminatory. We investigate how limited liability or the threat of sabotage influences the team's problem. It is further shown that players who earn higher wages can be worse off than teammates with lower wages and that present-biased preferences can mitigate procrastination.
Keywords: D82; M52; L22; J71; 330; moral hazard; team production; partnerships; procrastination; contract design; discrimination; Arbeitsgruppe; Projektmanagement; Zeitkonsistenz; Moral Hazard; Anreizvertrag; Theorie